Oysters and fish - Murrey, Thomas J. (Thomas Jefferson), 1844?-1900 (Salt Lake City, UT : Project Gutenberg, 2016)
"Oysters and Fish" by Thomas J. Murrey is a comprehensive cookbook focused on seafood, written in the late 19th century. The work offers a plethora of recipes and recommendations for preparing various types of seafood, specifically highlighting oysters and their many culinary applications. The author aims to enlighten readers on incorporating more fish into their diets, suggesting that these options can provide both variety and nourishment. At the start of the book, the author discusses the benefits of substituting fish for more common breakfast choices like steak and chop, advocating for the versatility of seafood dishes beyond frying or broiling. He elaborates on the oyster season, proper handling, and the culinary merits of oysters and other shellfish, providing insights into their life cycle and nutritional value. The opening sections encapsulate a mixture of practical advice and interesting anecdotes, setting the stage for the subsequent collection of recipes that celebrate the rich flavors and culinary potential of seafood. (This is an automatically generated summary.)
Release date is 2016-11-13
E-text prepared by the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Cooking (Fish); Cooking (Oysters)